Evaluation of the Activity of Olibanum Oil as an Immune Booster in Rats - Gharb, Lamiaa A.; Ismael , May K.; Qaddoori, Yasir B. (Iraqi Journal of Science, 2024)
The applications of herbal medicine have recently acquired growing interest in range of the prophylaxis and treatment of diseases. Olibanum has been used since ancient eras and several reports studied the pharmacological characteristics of boswellic acid, particularly their effect on the inflammatory response, analgesic properties, and anti-arthritic activity mostly in cell lines, but new approaches include animal models to assess these natural derivatives effects taking into consideration of being safer than synthetic preparations. The impact of olibanum oil on several parameters was studied in rats during this study. These included white blood cell (WBC) count, lactate dehydrogenase (LDH), and C reactive protein (CRP), as well as other pro-inflammatory cytokines like tumor necrosis factor alpha (TNF-α) and interleukin 6 (IL-6), and the cytokine interleukin -10 (IL-10) that is anti-inflammatory. Total WBCs in addition to IL-10 levels significantly increased in the oil-treated group in comparison with the control one, while the rats treated with olibanum oil revealed a significant reduced level of LDH, CRP, IL-6 and TNF- α compared with the controls (p < 0.05). These outcomes indicate that olibanum oil treatment are manifested by cytokine changes, it can improve the anti-inflammatory response and down-regulate the pro-inflammatory cytokines. So, the promising impact of olibanum oils as an immunomodulator could be used in alternative therapies.